Regulatory Uncertainty as A Challenge to The Protection of Foreign Investors’ Legitimate Expectations from The Perspective of Indonesian Investment Law - Arlansyah Harahap; Zulfikri Akramul Akbar; Duhita Driyah Suprapti; Sang Ayu Putu Rahayu (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the relationship between regulatory uncertainty and the protection of foreign investors’ legitimate expectations within the framework of Indonesian investment law. Employing a non empirical normative legal research design, the study integrates statutory, conceptual, and comparative approaches to evaluate the extent to which Indonesian investment regulations provide legal certainty consistent with internationally recognized investment protection standards. The analysis focuses on Law Number 25 of 2007 concerning Investment, Law Number 6 of 2023 concerning Job Creation, and Government Regulation Number 5 of 2021 concerning Risk Based Business Licensing, complemented by international investment law doctrines and comparative jurisprudence. The findings indicate that Indonesian law implicitly accommodates the protection of legitimate expectations through principles of legal certainty and equal treatment, yet lacks explicit normative recognition. Regulatory inconsistency, overlapping governance structures, policy transitions, and implementation disparities create conditions that weaken investor reliance and regulatory predictability. The study further identifies a normative gap between domestic regulatory practice and international standards of Fair and Equitable Treatment. Strengthening investor protection requires regulatory harmonization, evidence based regulatory review, institutional coordination, and investment governance mechanisms capable of ensuring greater stability, transparency, and legal coherence.